Correlates of University Adjustment Among Malaysian Students - Usmani, Aisha (2002)
The present study is intended for a better understanding of university adjustment of Malaysian adolescents. More specifically, the purpose of this research was to examine the factors contributing to the adjustment of these adolescents in the university. The target population was Bachelor students (Teaching English as a Second Language) at Universiti Putra Malaysia in the age range of 18 and 23 years. Since the population was only 178, the whole population was studied. Eleven respondents filled the questionnaires for the pilot study and a total of 150 subjects filled the questionnaires for the main study, but only 130 questionnaire sets were valid. The study is correlation in nature. Based on previous research studies and theories, nine independent variables were chosen to investigate their relationship with university adjustment. The Student Adaptation to College Questionnaire was used to measure university adjustment of Malaysian adolescents. The Self-Esteem Inventory and Coping Skills Inventory were used to study self-esteem and coping skills respectively. The Students Perception of University Student Services Inventory, developed by the researcher, was used to measure university factors. The study was limited to late adolescents and most of the respondents were female Malay Muslims. The analysis of the data showed, that most of the respondents had an average level on all the four components of university adjustment. A significant relationship was found between 35 of the 36 relationships studied. There was no significant relationship found between personal-emotional adjustment and academic advising. Coping skills and financial issues predicted all four components of university adjustment.